2016
DOI: 10.1136/annrheumdis-2016-209297
|View full text |Cite
|
Sign up to set email alerts
|

Antimodified protein antibody response pattern influences the risk for disease relapse in patients with rheumatoid arthritis tapering disease modifying antirheumatic drugs

Abstract: 2009-015740-42; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 46 publications
3
53
0
1
Order By: Relevance
“…Interfering with such triggers would allow retarding or even inhibiting the onset of the disease. Notably, currently available therapies for RA, such as cytokine (TNF and IL-6) blockers or inhibitors of the JAK-STAT pathway 43 , exclusively tackle the inflammatory phase of the disease but do not interfere with the underlying processes that initiate the onset of arthritis and therefore often need to be given life-long 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Interfering with such triggers would allow retarding or even inhibiting the onset of the disease. Notably, currently available therapies for RA, such as cytokine (TNF and IL-6) blockers or inhibitors of the JAK-STAT pathway 43 , exclusively tackle the inflammatory phase of the disease but do not interfere with the underlying processes that initiate the onset of arthritis and therefore often need to be given life-long 44 .…”
Section: Discussionmentioning
confidence: 99%
“…As for the second outcome, initial DFR, Figueiredo et al recently showed that patients with a broad pattern of AMPA response are at high risk of disease relapse in the first year after DMARD tapering [ 27 ]. Although the trend we found for initial DFR was significant for the number of AMPAs, our findings do not fully support Figueiredo’s observation that a broad autoantibody profile is unfavourable for DFR because we did not identify a dose-dependent effect.…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis, ARTISAN PCR and sequencing were performed as previously described 20 21. The same methodology using acetylated-vimentin (HC55) and lysine-vimentin (HC56)22 streptavidin-tetramers was used to isolate two AAPA-IgG sequences. The ACPA-IgG 7E4 sequence was provided by Dr Rispens, Sanquin, The Netherlands 23.…”
Section: Methodsmentioning
confidence: 99%